Road verges provide alternative habitats for some, but not all, meadow plants - Oldén Anna; Pitkämäki Tinja; Halme Panu; Komonen Atte; Raatikainen Kaisa J. (John Wiley & Sons Ltd, 2022)
Questions
Agricultural intensification has led to the decline of biodiverse meadows and other semi-natural grasslands. Road verges offer potential alternative habitats for meadow species, but they may not be suitable for all meadow species due to different soil properties, frequent disturbances, pollution or suboptimal management. Are their communities of vascular plants and bryophytes similar or dissimilar to those in mown or grazed meadows? What kind of species are associated with road verges, mown meadows or grazed meadows? How do the habitat types differ in their soil conditions and disturbance intensity?
Location
The study was conducted at 36 sites in central Finland.
Methods
We compared the vascular plant and bryophyte flora and the habitat characteristics of road verges, mown meadows and grazed meadows.
Results
The community composition of both vascular plants and bryophytes differed among the habitat types. Many species occurred in all three habitat types, but several meadow specialists were absent or less frequent in the road verges. In contrast, road verges hosted more forest species and ruderal species, especially bryophytes. Road verges differed from meadows in their soil conditions.
Conclusions
We conclude that although road verges may host some species typical to meadows, their value as alternative habitats could be increased by improved soil preparation and vegetation management. Meanwhile, the continued decline of quality habitats for meadow species underscores the need to maintain, increase and improve meadow management.